SPECIFICITY OF ANTIBACTERIAL ACUITY IN DISEASES OF THE LUNGS, ACCOMPANIED BY POSTCOVID SYNDROME, WHICH OCCURS IN CHILDREN - Muydinova Nargiza Muxtarjanovna (Web of Journals Publishing, 2024)
This article explores the specificity of antibacterial treatment of lung diseases in children with post-COVID syndrome. The focus is on understanding specific bacterial profiles, therapeutic responses, and outcomes in post-pediatric covid cases. Comprehensive analysis of the existing literature, combined with empirical methods and results, provides the basis for discussions and conclusions aimed at improving treatment protocols.
Keywords: antibacterial tension, lung diseases, post-covid syndrome, Pediatrics, therapeutic response, bacterial profiles.